"Whose job is it anyway?": Secondary English Language Arts teachers' literacy-centered professional development in rural, suburban, and urban contexts - Cox, Rachael Elizabeth (My University, 2026)
Literacy instruction has been part of both a critical and public conversation for the past 80 years (Thomas, 2022), as experts and lay people weigh in on how we should be teaching children to read. “The Reading Wars,” invokes imagery of battle: the clash of whole language vs phonics instruction. In 2018, the reading wars were re-ignited with Emily Hanford’s article “Why Aren’t Kids Being Taught to Read?” While criticism and conversation have centered early readers, secondary students also struggle with literacy and need support. Often left out of the conversation, secondary English teachers do not always feel prepared to offer this support (Lillge, 2019). Professional development and training offer one way for secondary English teachers to feel better prepared to address these issues. However, access to these opportunities can vary based on the resources and contexts within a school district, and teachers may find themselves seeking professional development opportunities on their own. The purpose of this study is to explore how in-service secondary English teachers describe their literacy related professional development opportunities, barriers, and the impact of the professional development on their teaching praxis within rural, suburban, and urban contexts within the state of Kansas. The data for this dissertation research was collected under a grant-funded research project to improve literacy outcomes in Kansas, with a long-term goal of creating resources for Kansas educators to better support literacy practices and to describe the landscape of literacy education in the state of Kansas. My own dissertation research draws from this larger dataset conducted in this grant work. I used a convergent, parallel mixed-method approach (Creswell, 2014; Castro et al., 2010). My data included 11 closed-ended Likert questions asking teachers about their feelings of self-efficacy regarding literacy topics. This data also included one-open ended qualitative survey question, as well as a follow-up interview with 11 participants further exploring teachers’ experiences with literacy focused professional development. The data was analyzed in several phases. First the closed-ended survey question was analyzed to look for variance among self-efficacy levels in teachers in rural, urban, and suburban settings (Creswell, 2014). Drawing on Braun and Clarke’s (2022) six phases for Thematic Analysis, open and axial coding of the qualitative open-ended survey question and interview transcripts resulted in 6 categories, and 163 codes in the survey, and 6 categories and 104 codes in the interview. Finally, the qualitative codes were analyzed quantitatively to look for differences in code frequencies between the rural, urban, and suburban contexts (Johnson & Christensen, 2012). Sociocultural Theory serves as my theoretical framework for analysis (Lewis et al., 2013; Vygotsky, 1978). I used two supplementary structural models to further analyze and contextual professional development experiences in different teaching contexts. I drew on a professional development framework (Darling-Hammond et al., 2017; Desimone, 2009; Guskey 2003; 2014), as well as Shanahan’s (2005) National Reading Panel Report to discuss topics and quality of the professional development opportunities that teachers encounter. Results indicated that while PD is a universal experience across the state, rural teachers receive less frequent and less-focused PD than teachers in urban and suburban contexts. State-sponsored literacy measured supported equitable access to PD for all teaching contexts.
Keywords: Mixed-methods; Literacy; Professional development; Secondary literacy; Self-efficacy; Science of reading